Complications of drowning: A case report - Felicia Anita Wijaya; I Gde Doddy Kurnia Indrawan (Indonesian Pediatric Society, 2019)
Unintentional drowning is the sixth most common cause of accidental death, accounting for 4,086 deaths (1.4 per 100,000) in the United States in 2007.1 In children, drowning is the second leading cause of injury-related death, and those aged 1-3 years have the highest rate of drowning.2 More than 1,400 pediatric drownings were reported in the United States in 2008.3 Many drowning deaths are due to lack of supervision in the bathtub, unprotected access to a pool, or lack of swimming skills.3 For every death by drowning, six children are hospitalized for drowning, and up to 10% of survivors experience severe brain damage.2